The competency criteria of Building Information Modelling (BIM) managers among construction stakeholders in Malaysia / Nurmazlina Nabilah Mohd Azmi - Mohd Azmi, Nurmazlina Nabilah (2022)
BIM offers numerous advantages that can assist contractors in managing their projects effectively and effortlessly. BIM has the potential to be widely adopted in the construction industry and to be expanded into the architecture, engineering, and construction (AEC) industry. Malaysian Government through CIDB has been promoting the use of BIM since 2013 and it had been proven through various research that the adoption of BIM in the construction industry has many benefits and challenges to the stakeholders. A review of the literature finds a lack of research that focuses on the competencies of BIM managers in Malaysia. Therefore, this research aims to identify the common and most important competencies for BIM managers among construction stakeholders in Malaysia. This research applied Individual BIM Competencies (IBC) approach and of having been categorized into eight competencies variables: managerial, administrative, functional, operational, technical, implementation, supportive, and research and development. The data of this study were collected through an online questionnaire survey that was distributed by e-mail and WhatsApp to 63 companies registered with CIDB myBIM Centre.